Comparative Study of Growth Hormone Treatment in Children with Idiopathic Short Stature and Growth Hormone Deficiency - Rim Jeong, Hwal; Byul Kwon, Eun; Seok Shim, Young; Sang Lee, Hae; Soon Hwang, Jin (Current Drug Metabolism, 2015)
Background/Aims: Idiopathic short stature (ISS) is defined as short stature of unknown origin. Responses to growth hormone (GH) in children with ISS are highly variable and dose-dependent, and the optimal treatment is controversial. This study was performed to compare the effects of GH treatment in prepubertal children with ISS versus growth hormone deficiency (GHD). Methods: This retrospective study was conducted at Ajou University Hospital, Korea. Children with GHD (n = 38) or ISS (n = 22) were treated with GH (0.23 mg/kg/week, 6 times a week) for 2 years. All subjects were prepubertal during the study period. The auxological parameters and growth outcome of the two groups were compared. The association of initial clinical characteristics and first-year height standard deviation scores (Δ height SDS) was analyzed. Results: No differences were observed in the baseline auxological parameters between the ISS and GHD groups. Growth outcomes in the first and second years were similar in both groups. Age was negatively associated with first-year change in Δ height SDS in both groups. Conclusions: GH treatment was effective in both children with ISS and those with GHD. Early intervention with GH is the most appropriate therapeutic option in both ISS and GHD.
Keywords: Growth hormone